ANALISIS BISNIS INTERNAL DENGAN METODE CRITICAL SUCCESS FACTORS (CSF) DAN VALUE CHAIN (STUDI KASUS PT. FARMASI X) - Nur Hayati (Fakultas Ilmu Komputer, 2016)
PT. Pharmacy X is one of Indonesia’s best-regarded manufactures of ethical medicine. It also manufactures “Naspro”, then well-known analgesic. As one of the companies which had stood since 1948 in the era of trace competition today, PT. Pharmacy X seeks to maintain and even more improve the quality of the products it produces so that it can survive and be able to develop products up to a better level again. For this matter, a decision taken by a leader of great influence on the success of an organization to achieve its goals, and it needs a proper method to analyze the objective factors that influence the success or failure in achieving that goal. Methods of Critical Success Factors (CSF) and CSF analysis is used by PT Pharmacy X to interpret the objects more clearly, to define the activities, and carried out every information’s needed. CSF can be determined if the objective or the direction and objectives of the organization have been identified. Destination PT. Pharmacy X is entered in 60 large pharmaceutical company in IMS-ITMA version. In addition to CSF, Value Chain analysis is also used in line with the CSF analysis that is useful to identifying the most critical processes, and provide a focus on achieving goals through actions or the most appropriate process to be implemented. The main activity is the most important factor in realizing the goal of PT. Pharmacy X, such as material ordering, forecasting sales, orders received from distributors, production processes, delivery of goods to a distributor, create demand, sales monitoring, evaluation and monitoring of stock sales.